El ámbito temporal del Reglamento Europeo de Sucesiones y la (in)validez de las voluntades conjuntas en atención al derecho polaco. Comentario a la sentencia del Schleswig Higher Regional Court del 25 de abril de 2016, 3 wx 122/15 - Nasse, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The European Succession Regulation (Regulation (EU) No 650/2012) entered into force on 16 August 2012 and applies since 17 August 2015. To facilitate the application of the Regulation, the German legislator introduced a “Law on International Succession Law and the Amendment of Provisions on Certificates of Inheritance and other areas”. One aspect of the new German law is the amendment of Article 25 of the Introductory Act to the German Civil Code (EGBGB) which now provides that chapter III of the Succession Regulation shall also apply to successions that do not fall within the Regulation’s scope of application. In its decision, the Schleswig Higher Regional Court found that Article 25 EGBGB only extends the material but not the temporal scope of the Regulation. Furthermore, it discussed the characterization of the Polish prohibition of joint wills and found that the joint will of a Polish citizen who had been living in Germany is valid under the applicable German law.